Geospatial science and technology for development, with a focus on urban development, land administration and disaster risk management (UN New YorkUS, 2012)
Explores the ways in which geospatial science and technology, i.e. the tools and methodologies that are used to collect, manage and analyse geospatial data (GS&T), can support development. Includes topographic data, land property records, spatial plans, soil and forest survey inventories, and a variety of geographically referenced social and and economic data such as population characteristics.
Bibliography: p.49-54.